PEMBERDAYAAN REMAJA BERBASIS ONLINE SEBAGAI PROMOTOR KESEHATAN JIWA - Forman Sidjabat; Rachelda Bella Alycia Macado; Widya Puspitasari; Dhea Alayda Akrima; Octawayaning Marvionada; Indi Toto Paniulin; Tiana Kuntari; Nevira Anis Subagio; Rizky Zahra Nurfajri Sabarno Zahra Nurfajri Sabarno (COVIT (Community Service of Health), 2022)
Adolescents are a group that is vulnerable to mental health problems because they are in the developmental stage. This online-based youth empowerment activity is aims to increase adolescents knowledge and skills in promoting mental health using social media. This empowerment activity is carried out online using social media whatsapp, instagram and zoom meeting. The youth empowerment process is packaged in the form of Gen Z Online Camp during August 9-17, 2021. The targets of this activity are representatives of youth at SMA Negeri 5 Sorong, Papua, SMK Negeri 1 Plosoklaten, Kediri Regency and SMK Negeri 2 Tarakan, North Kalimantan. The results of this activity from 49 participants 61.3% experienced an increase in knowledge (p value <0.05), able to produce mental health promotion media. The use of social media has proven to be effective for youth empowerment activities as health promoters. Â  Keywords: Instagram, Mental Health, Adolescents, Online-based Empowerment. Â